CDI of the ovaries - Rupprecht, Thomas; Deeg, Karl Heinz (Springer International Publishing, 2015)
There are three common indications for the colour sonographic investigation of the ovaries in the paediatric age group. Abdominal pain in the lower quadrants suggesting ovarian torsion or inflammation, the evaluation of an ovarian mass seen as an incidental finding in abdominal sonography and finally the evaluation of suspected inguinal herniation. Colour Doppler imaging has in most cases a sufficient grade of diagnostic accuracy to be the sole imaging modality.
CRIS-Team Scopus Importer:2025-03-05